2014
DOI: 10.1007/s00432-014-1711-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade dietary-related inflammation and survival after colorectal cancer surgery

Abstract: PurposeProlong inflammation is a central process observed in several chronic conditions and may be responsible for survival. There is an increasing evidence showing the role of diet in inflammation and habitual diet may be responsible for low-grade inflammation. The purpose of our study was to assess the effect of inflammatory properties of habitual diet measured by the Dietary Inflammatory Index (DII) on survival among surgical patients treated for colorectal cancer (CRC).MethodsA follow-up study among 689 CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…This trend toward a lack of association with longer survival time could confirm our results of no association between DII score (on average assessed 6 years after diagnosis) and mortality after a median follow‐up time of 7 years in the overall sample. However, the previous study only observed associations in patients without distant metastases who had undergone surgery and chemotherapy which is in contrast to our findings of a stronger association between the DII and risk of dying in those CRC survivors with metastases. In addition, the former study assessed dietary behavior prior to CRC surgery after hospital admission which is likely to occur relatively soon after diagnosis and which is different to our diet assessment at a median of 6 years after CRC diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This trend toward a lack of association with longer survival time could confirm our results of no association between DII score (on average assessed 6 years after diagnosis) and mortality after a median follow‐up time of 7 years in the overall sample. However, the previous study only observed associations in patients without distant metastases who had undergone surgery and chemotherapy which is in contrast to our findings of a stronger association between the DII and risk of dying in those CRC survivors with metastases. In addition, the former study assessed dietary behavior prior to CRC surgery after hospital admission which is likely to occur relatively soon after diagnosis and which is different to our diet assessment at a median of 6 years after CRC diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to this growing number of studies that investigated the association between dietary inflammatory potential and the risk of new‐onset (incident) CRC, the association between post‐diagnosis DII score and mortality in long‐term CRC survivors is a relatively novel area of research. To our knowledge, only one previous study ( n = 689) examined the association between low‐grade diet‐related inflammation (measured by the DII) and survival after CRC . The authors observed a statistically significant association between the DII and an increased risk of mortality only at time points 1 and 3 years after CRC surgery, not at 5 years after surgery, and not in overall survival.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In practice, the DII score is usually computed from dietary intake assessed using a validated FFQ or from historical dietary records. Apart from the significant association of the DII score with CRC risk, the DII score could also be used to predict the prolonged hospitalization and survival among CRC patients treated surgically [ 21 , 22 ]. However, no statistically significant associations were found between a pro-inflammatory diet and the risk of colorectal adenoma recurrence [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the updated version, several studies have found associations between DII score and CRP, in adults and seniors [26], and IL-6, tumour necrosis factor-alpha (TNF-α) and another score of combined inflammatory biomarker in postmenopausal women [27]. The DII score has been used in several studies to predict mortality [28,29], survival [30], and diseases, especially cancer [30,31], but also obesity [32], cardiovascular disease [33] and metabolic syndrome [32,34].…”
Section: Introductionmentioning
confidence: 99%